Mollison's blood transfusion in clinical medicine - Klein, Harvey G.; Anstee, David J. (Chichester, West Sussex, UK : Wiley-Blackwell, 2014)
'Mollison's Blood Transfusion in Clinical Medicine is an icon in the field of transfusion and the first edition was published in 1951. The book arose from the concept of the transfusionist, as both scientist and expert consultant. For many years, this text has provided the primary, and often the sole, reference for detailed information and practical experience in blood transfusion. The book is completely revised and updated throughout to include the latest advances and developments in the field'--Provided by publisher.
Storage of red cells in the liquid stateCollection of blood to provide components; Storage of red cells in the frozen state; The transfusion of red cells in anaemia; 10 Red cell incompatibility in vivo; Qualitative aspects of red cell destruction by alloantibodies; Quantitative aspects of the destruction of transfused red cells by alloantibodies; Destruction of transfused red cells without serologically demonstrable antibodies; Destruction of recipient's red cells by transfused antibodies; 11 Haemolytic transfusion reactions; Intravascular destruction.
Blood donors and the withdrawal of blood -- Transfusion of blood, blood components and plasma alternatives in oligaemia -- Immunology of red cells -- ABO, H, LE, P, GLOB and I Blood Group Systems -- The Rh blood group system (including LW and RHAG) -- Other red cell antigens -- Red cell antibodies against self- antigens, bound antigens and induced antigens -- Blood grouping techniques -- The transfusion of red cells -- Red cell incompatibility in vivo -- Haemolytic transfusion reactions -- Haemolytic disease of the fetus and the newborn -- Immunology of leucocytes, platelets and plasma components -- The transfusion of platelets, leucocytes, haematopoietic progenitor cells, and plasma components -- Some unfavourable effects of transfusion -- Infectious agents transmitted by transfusion -- Exchange transfusion and haemapheresis -- Alternatives to allogeneic transfusion -- Plasma fractionation and fractionation products.
Includes bibliographical references and index.
Online resource; title from electronic title page (ebrary, viewed on August 3, 2015).
Keywords: Blood -- Transfusion; Blood Transfusion; Blood Transfusion; MEDICAL -- Pharmacology; Blood -- Transfusion; Electronic books; Electronic books